GAMBARAN PERTUMBUHAN BAYI YANG LAHIR DENGAN BERAT BADAN LAHIR RENDAH (BBLR) PASCA HOSPITALISASI - Nuremsita " "; Riri " Novayelinda; Sofiana " Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Babies of low birth weight (LBW)  are baby that born with weight less than 2500 gram. LBW are susceptible to nutritional problems, thermoregulation problem, immaturity of organ function, potential of slow growth and high risk of morbidity. The purpose of this study was to describe the growth of babies with LBW after hospitalization. This research was a descriptive study with cross-sectional design. The research was done in Arifin Achmad General Hospital Pekanbaru. The sample of this research were taken by total sampling technique about 42 respondents because from 60 respondents, 18 respondents had unclear address, the number of handphone couldn’t be called and the babies have died. The data was collected by an observation sheet. The analysis used univariate analysis. The results showed that 25 respondents (59.5%) were under, 12 respondents (28.6%) were good growth and 5 respondents (11.9%) were poor growth. Based on body length/age, most of respondents were short growth  about 25 respondents (59,5%), normal growth were 13 respondents (31,0%) and very short growth were 4 respondents (9.5%), for head circumferenceare/age were obtained all respondents in the normal category about 42 respondents (100%), so it could be concluded that most of babies impaired growth weight and body length but normal for head circumference. The results of study could be used as baseline information to do further research about factors that affect the care of babies with LBW in the house. Keywords  : Growth,infant, low birth weight